THE ADVANTAGES OF PUBLIC AUCTIONS FOR COMPANIES IN FORESTRY - Đurić, Slađana (Journal of process management and new technologies, 2019)
JP “Vojvodinašume” Petrovaradin, Šumsko gazdinstvo „Sremska Mitrovica“ Sremska Mitrovica isprimary engaged in activities of management, maintenance, regeneration and protection of forests, as the natural resource, but also performs activities related to exploitation and utilization of forests. The Company finances its activities independently by selling its own timber assortments and services that are the result of its management performance. Timber assortments are sold through regular contracts for industrial buyers, independent contracts for companies and citizens, and in public auctions. This paperwork is to inform the public about timber auctions in this Company and to popularize this method of sales of timber assortments, as the method of selling product at prices higher than prices defined in actual price-list.